PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR - AYU RAHAYU, EKA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: Working capital has the most liquid several components that is cash, receivables and inventory. There is relationship between efficiency of working capital management and company profitability. This research of aimed to understand the influence of cash turnover, receivable turnover and inventory turnover to profitability of manufacture company. The population are all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2008-2012. There are 10 companies selected using purposive sampling method. The use of analysis technique is that Multiple Regression Analysis.Using is hypothetical test with F-test and t-test. The result shows that there are 2 variables: Cash turnover and Receivable turnover which have no significant effect on ROA. Inventory turnover which have significant impact on ROA. These result show that only inventory turnover which effect to profitability. In the other hand, cash turnover and receivable turnover have no significant effect in achieving profit at manufacturing company. Keyword:cash turnover, receivable turnover, inventory turnover and profitability.